2012
DOI: 10.1111/j.1582-4934.2011.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin activates heme oxygenase‐1 at the stress response elements

Abstract: Statins are known to inhibit growth of a number of cancer cells, but their mechanism of action is not well established. In this study, human prostate adenocarcinoma PC-3 and breast adenocarcinoma MCF-7 cell lines were used as models to investigate the mechanism of action of atorvastatin, one of the statins. Atorvastatin was found to induce apoptosis in PC-3 cells at a concentration of 1 μM, and in MCF-7 cells at 50 μM. Initial survey of possible pathway using various pathway-specific luciferase reporter assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…These effects were also caspase-dependent since simvastatin increased caspase-3 and -9 activity in MDA-MB231 cells39. Similarly, fluvastatin and atorvastatin, were also reported to induce dose- and time-dependent apoptosis in MCF-7 and MDA-MB-231 breast cancer cell lines4041. Several mechanisms have been proposed for statin-induced cell death in breast cancer cells including an increase of reactive oxygen species (ROS)42, the downregulation of survivin expression43, increased nitric oxide synthase activity (iNOS or NOS II) via geranylgeranylation44, and G1/S cell cycle arrest due to an increase in p21(Waf1/Cip1)45.…”
Section: Discussionmentioning
confidence: 93%
“…These effects were also caspase-dependent since simvastatin increased caspase-3 and -9 activity in MDA-MB231 cells39. Similarly, fluvastatin and atorvastatin, were also reported to induce dose- and time-dependent apoptosis in MCF-7 and MDA-MB-231 breast cancer cell lines4041. Several mechanisms have been proposed for statin-induced cell death in breast cancer cells including an increase of reactive oxygen species (ROS)42, the downregulation of survivin expression43, increased nitric oxide synthase activity (iNOS or NOS II) via geranylgeranylation44, and G1/S cell cycle arrest due to an increase in p21(Waf1/Cip1)45.…”
Section: Discussionmentioning
confidence: 93%
“…The enhancer-luciferase reporter plasmids were constructed by inserting sequences of various synthetic response elements into the filled-in Nhe I /Bgl II sites of pGL3-promoter vector (Promega, Madison, WI, USA) or Eco RV site of pGL4-promoter vector via blunt-end ligation as described in our earlier study [15]. Internal control plasmid, pGL4.74[hRluc/TK], was purchased from Promega (Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it even suppressed the induction of HO-1 by statins or lipopolysaccharide [14]. In our earlier study, ZnPP was found to induce HO-1 expression in human prostate adenocarcinoma PC-3 and breast adenocarcinoma MCF-7 cells [15]. It is a much stronger inducer of HO-1 than atorvastatin, one of the statins.…”
Section: Introductionmentioning
confidence: 99%
“…They are also known to increase atherosclerotic plaque stability, to improve endothelial function and to have an anti-oxidant effect and anti-inflammatory activity [12]. According to some studies that investigate the antioxidant and anti-inflammatory effect of statins, atorvastatin activates heme oxygenase-1 at the stress response elements in prostatic cancer cells and breast cancer cells [13]. Simvastatin decreases reactive oxygen species level by Nrf2 activation via PI3K/Akt pathway in primary mouse embryonic fibroblasts from wild-type or Nrf2 knockout C57BL6J mice and ST-2 cells [14].…”
Section: Introductionmentioning
confidence: 99%